ANALISIS IMPLEMENTASI SAK- ETAP PASCA PENCABUTAN PSAK NO.27 PADA KPRI DI KABUPATEN PURWOREJO - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2020)
Indonesian Accounting Standard for Non-Publicly-Accountable Entities (IAS for SMEs) is a standard report writing for Small and Medium Interprise (SME) but publish general purpose financial statements for external users. IAS for SMEs effective applies force on 1 January 2011 after the issuance of the revocation ED PPSAK 8 FASB Statement No. 27. 2014 is the fourth year of the enactment of IAS for SMEs. So that the researcher intends to analyze the extent to which the implementation of IAS for SMEs after revocation FASB Statement No. 27, especially on KPRI in Purworejo. Not just the studied implementation but the extent to which the government socialization to introduce IAS for SMEs to the cooperative movement. The research method used in the study is a qualitative research method with purposive sampling technique obtained six KPRI as research samples. The technique of collecting data through observation, interviews and document study and tested the validity of the data by testing credibility and transferability. The results of the study by interviewing informants who have been determined and direct observation showed that KPRI in Kabupaten Purworedjo IAS for SMEs not use guidelines. They are still using the old guidelines of FASB Statement No. 27. Problem occurred because of government Purworejo not provide socialization IAS for SMEs whereas the cooperative movement in 2014 was the fourth year IAS for SMEs is effective, it should have a thorough use of IAS for SMEs on small and medium interprise as KPRI. Keywords: SAK ETAP, KPRI, Financial Accounting